The Apotropaic "Witch posts" of Early Modern Yorkshire: A Contextualization. (2nd January 2018) - Angus, Bill
Abstract: In houses in Yorkshire there remain carved posts of some antiquity, marked with a distinct X, whose provenance is unknown. These are known locally as "witch posts." Understanding these as examples of apotropaic folk-belief is recommended by contemporary accounts of the necessity of protection against evil by charms, images, and objects. Such beliefs were not only not marginal but actively encouraged by both traditional church practices and a Neoplatonic conception of the potency of words, incantations, and charms in physical and spiritual matters. That these ideas have resisted the pressure of the skeptical and rational discourses with which they have been approached is partly testament to the shifting signification of the posts themselves.